2015
DOI: 10.1016/j.jadohealth.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Cultural Stressors and Effects on Mental Health and Substance Use Among Hispanic Immigrant Adolescents

Abstract: Purpose We sought to determine the extent to which initial levels and over-time trajectories of cultural stressors (discrimination, negative context of reception, and bicultural stress) predicted well-being, internalizing symptoms, conduct problems, and health risk behaviors among recently immigrated Hispanic adolescents. Addressing this research objective involved creating a latent factor for cultural stressors, establishing invariance for this factor over time, estimating a growth curve for this factor over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
131
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 28 publications
8
131
0
1
Order By: Relevance
“…Our data suggest that, on average, parent acculturation stress was highest within the first five years that parents settled into their receiving communities and decreased over time. These findings corroborate research on the development of acculturation stress in recent immigrant Latino youth, in which acculturation stress also decreased over time (Schwartz et al, 2015). Although earlier levels of and change in acculturation stress negatively influenced family functioning and Latino youth mental health and substance use, our data suggests that preventive interventions that focus on acculturation stress and/or family functioning may be especially beneficial during the first five years following immigration (when acculturation stress was highest), but can also be beneficial later in the settlement process.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our data suggest that, on average, parent acculturation stress was highest within the first five years that parents settled into their receiving communities and decreased over time. These findings corroborate research on the development of acculturation stress in recent immigrant Latino youth, in which acculturation stress also decreased over time (Schwartz et al, 2015). Although earlier levels of and change in acculturation stress negatively influenced family functioning and Latino youth mental health and substance use, our data suggests that preventive interventions that focus on acculturation stress and/or family functioning may be especially beneficial during the first five years following immigration (when acculturation stress was highest), but can also be beneficial later in the settlement process.…”
Section: Discussionsupporting
confidence: 87%
“…Parent acculturation stress was associated with worse adolescent-reported family functioning, which in turn, predicted lower symptoms of depression, lower aggressive behavior, and higher self-esteem in youth. These results reinforce and extend prior research on the harmful effects of acculturation stress on Latino youth well-being when youth themselves experience these stressors (Schwartz et al, 2015). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings about cigarette and marijuana use are consistent with studies suggesting that stress is implicated in the initiation and escalation of substance use during adolescence (Brady & Sinha, 2005; Hoffmann, Cerbone, & Su, 2000; Nation & Heflinger, 2006; Newcomb & Harlow, 1986; Schwartz et al, in press; Wills, Sandy, Yaeger, Cleary, & Shinar, 2001). These findings also concur with studies that have identified low parental involvement as a risk factor for adolescent substance use factor (Dishion et al, 2004; Prado et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Family dysfunction (Moretti, Obsuth, Odgers, & Reebye, 2006;Tremblay et al, 2004), social disadvantage (Reboussin, Hubbard, & Ialongo, 2007;Tremblay et al, 2004), cultural stressors (Schwartz et al, 2015), childhood physical or sexual abuse (Barnow, Lucht, & Freyberger, 2001;Cullerton-Sen et al, 2008;Stevenson, 1999), PTSD (Moretti et al, 2006;Taft, Schumm, Orazem, Meis, & Pinto, 2010), parental substance abuse (Delaney-Black et al, 2000), exposure to violence (Boxer et al, 2008), and poor self-control (Derefinko, DeWall, Metze, Walsh, & Lynam, 2011) can all increase the likelihood of aggressive behavior in childhood or adolescence. Among adults seeking treatment for substance use problems, early maladaptive schemas-stable, enduring, dysfunctional interpersonal themes-predicted different forms of aggressive behavior, independent of substance use, antisocial personality, age, and education (Shorey et al, 2015); this pattern may extend to adolescents as well (Muris, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%